Sikap Sayyid Qutb terhadap Tafsir Ilmi - hasfifin09 hasfifin (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
The modern era is a time when the interpretation of ilmi develops so rapidly. The appearance of this style of interpretation cannot be separated from the supporters or those who reject it. At this time also, many researchers and even scholars debated the views of Sayyid Qutb on the ilmi interpretation. This article seeks to examine and reveal how Sayyid Qutbs views on the tafsir ilmi style and how he interpreted the kauniyah verses. This type of research includes library research (library research) with a qualitative research approach. The main source of this research is his tafsir book Fi Zilal al Quran. This article then shows the conclusion that Sayyid Qutb is inconsistent between his theory and practice. In interpreting the kauniyah verses, Qutb repeatedly referred to scientific theory as a non-final meaning. Al Quran as an absolute essence, should not be subject to the results of scientific discoveries that are relative. However, it turned out that Qutb also used scientific theory in his interpretation to gain a better understanding.